Analysis of the Impact of Fisheries and Maritime Investment on the Indonesian Economy with the Interregional Input Output (IRIO) approach - Yullian Haumahu (Journal of Economic Education, 2023)
To analyze the impact of fisherseries and marine investment on the economy with an interregional input output (IRIO) approach. This research uses an interregional input output (IRIO) approach. The secondary data used are ten provinces of Maluku and the IRIO tables obtained from the Central Statistics Agency. The data analysis used are the analysis of the IRIO model approach, needs analysis and investment impact analysis. The results show that the sectors included in the marine sector have a positive role in the regional economy in Indonesia. This is obtained from the degree of coefficient of direct and indirect linkage both to the backward and to the future. Marine development policy through increasing the final demand component () of marine has a positive impact on the economy and regional economy in Indonesia both sectorally and spatially.